IoT Based Smart Alert Network Security System Using Machine Learning (International Journal of Innovative Research in Computer Science & Technology, 2023)
The increasing security threats in public  places such as airports, train stations, and shopping malls  require the development of smart security systems that can  detect potential threats and provide timely alerts to security  personnel. This research paper proposes an IoT-based  smart alert network security system using machine  learning to enhance public safety. The system integrates  various sensors and devices that collect data such as  motion, which is analyzed using machine learning  algorithms to detect anomalies and trigger alerts if any  suspicious activity is detected. The proposed system  achieves an accuracy rate of 91.12% in detecting  suspicious activities, which is significantly higher than the  existing security systems used in public places. The system can provide real-time alerts, which can reduce the response  time of security personnel and prevent potential security  threats. The proposed system can be implemented in  various public places to enhance public safety and prevent  security breaches. The results of this research paper  provide a useful reference for future studies on the  development of smart security systems using IoT and  machine learning technologies.
Keywords: Cloud; Face Recognition; KNN; IOT; Network